P499 Exclusive enteral nutrition induces transmural healing in adults with active Crohn's disease. (30th January 2023) - Chu, M; Day, A; Mathias, R; Direen, T; Broad, L; Lynch, K; Bryant, R
Abstract: Background: Exclusive enteral nutrition (EEN) is a nutrition-based therapy for active Crohn's Disease (CD). Transmural healing is a novel therapeutic paradigm in CD, holding benefit beyond endoscopic mucosal healing. There are limited data exploring EEN and transmural healing in CD. We aimed to examine the effect of EEN on inducing transmural response and healing as assessed by intestinal ultrasonography (IUS). Methods: This was a prospective, multi-centre, open-label cohort study. Adults ≥18 years with active CD were enrolled between March to September 2022. Eligible, consenting participants were nutritionally assessed by a specialised IBD dietitian and prescribed 6 weeks of EEN therapy. A 1.5kcal/ml polymeric, low lactose, fibre-free formula was used and EEN prescriptions were personalised to 25-30kcal/kg IBW and 1.2-1.5g protein/kg IBW/day. Patients were allowed concurrent tapering corticosteroid therapy and biological therapy. Participants completed clinical, biochemical and nutritional assessments at weeks 0, 3 and 6 and IUS at weeks 0 and 6. This included Harvey Bradshaw Index (HBI), C-Reactive protein, faecal calprotectin (FCP), body mass index (BMI). IUS assessment was conducted at baseline and at week 6 and images were centrally read by a blinded, IUS-trained gastroenterologist. Transmural response was defined by ≥25% bowel wall thickness (BWT) reduction from baseline. Transmural healing was defined as BWT≤3mm, Doppler signal score≤1, normal bowel wall stratification, and absence of inflammatory fat. Results: Fourteen patients, 9 were female (64.3%) and mean age of 44.4 years, were consecutively enrolled and completed 6-weeks of EEN therapy. Ten patients (71.4%) had ileal disease (L1), 4/10 had ileocolonic (L3) and predominant phenotype was inflammatory (B1, 7/14) and stricturing (B2, 6/14) disease. Mean disease activity was HBI 5.1±4.0.Two patients had perianal disease (14.3%). Nine patients (64.3%) reported 100% adherence and 4 patients (28.6%) reported 75-99% adherence to the exclusive diet by predefined adherence categories. At week 6, 11/14 (78.6%) of patients achieved clinical remission with 12/14 (85.7%) showing clinical response. Reductions in CRP and FCP were not statistically significant. Numerical reduction in BWT was observed 5.6±1.4mm vs 4.8±2.1mm (95% CI -1.94, 0.265, p = 0.124). Transmural response was achieved in 8/14 (57.1%) and transmural healing was reached in 2 (14.3%) patients. Most common side effect was constipation (42.9%). Conclusion: EEN was identified to induce early transmural response and healing in patients with active CD. Further studies are required to evaluate the capacity for EEN to induce transmural healing and the role of IUS as an early assessment tool in monitoring therapeutic response in CD.